THE INFLUENCE OF DIGITAL MARKETING ON CONSUMER BUYING INTEREST AT THE ABAYA FASHION SHOP - Zulkarnain, Rizal (Universitas Banten Jaya, 2024)
Technological conditions continue to develop, new things happen in our daily lives, and things that usually do not exist become available and liked by many people. One of them is the Internet. Currently, small to large businesses are taking advantage of developments in internet-based digital technology. The use of digital marketing that is carried out appropriately, consistently and attractively will have an impact on increasing purchasing interest in the products offered. The aim of this research is to determine the impact of digital marketing on purchase intentions. The methodology used is quantitative, with data obtained from questionnaire surveys and non-probability sampling techniques. Research analysis shows that digital marketing has a positive impact on purchase intentions.